PENGARUH KEMITRAAN USAHA TERHADAP KINERJA USAHA PADA USAHA KECIL MENENGAH (UKM) DAN KOPERASI DI KABUPATEN JENEPONTO SULAWESI SELATAN - Saparuddin M; Basri Bado (Jurnal Ilmiah Econosains, 2011)
ABSTRACT The objectives of this study are to determine the effect of the business partnership among small and medium business, government, banking, and other institutions, in the area of marketing, development of human resources, access to capital, and managerial organization toward financial business performance and non financial business performance in Jeneponto, South Sulawesi. This is a descriptive qualitative and quantitative research by using survey, random sampling techniques, with 21 businesess units as sample. Library study, observation, and questionnaires were used to collect the primary and also secondary data. Path analysis was used to analyze the data. The results of this study showed that simultaneously and partially, business partnership among small and medium business, government, banking, and other institutions in the area of marketing, development of human resources, access to capital, and managerial organization have significant positively effect on financial and non financial business performance. The finacial business performance was most influenced by the development access human resources aspect, and the non-financial business performance was most influenced by managerial organization aspect.Keywords: Partnership of business, financial business performance, non-financial business performance